2007
DOI: 10.1093/aje/kwm334
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Association between Perceived Discrimination and Hypertension in African-American Men and Women: The Pitt County Study

Abstract: Few studies have examined the impact of the frequency of discrimination on hypertension risk. The authors assessed the cross-sectional associations between frequency of perceived racial and nonracial discrimination and hypertension among 1,110 middle-aged African-American men (n = 393) and women (n = 717) participating in the 2001 follow-up of the Pitt County Study (Pitt County, North Carolina). Odds ratios were estimated using gender-specific unconditional weighted logistic regression with adjustment for rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
69
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 37 publications
5
69
0
Order By: Relevance
“…Discrimination has been associated with more depressive symptoms (34), poorer mental health (4-6, 17), poorer sleep (35,36), increased adiposity (12)(13)(14)37), higher blood pressure (9)(10)(11), inflammatory biomarkers (15,16), and subclinical CVD (7,8). However, studies of discrimination and CVD risk factors are not unequivocal (2,17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Discrimination has been associated with more depressive symptoms (34), poorer mental health (4-6, 17), poorer sleep (35,36), increased adiposity (12)(13)(14)37), higher blood pressure (9)(10)(11), inflammatory biomarkers (15,16), and subclinical CVD (7,8). However, studies of discrimination and CVD risk factors are not unequivocal (2,17).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies examining discrimination and CVD risk factors have clearly distinguished between race-based and nonracial discrimination. Studies that also evaluated racial/ethnic discrimination and CVD risk factors have generally not shown a stronger relationship for racial/ethnic discrimination than for overall perceptions of discrimination (7)(8)(9). Notably, no prior studies have investigated perceived discrimination or racial/ethnic discrimination in relation to incident CVD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[61][62][63] High levels of stress, being worried about HTN, experiencing adverse effects of antihypertensive medication, older age, self-reported medication nonadherence, and a HTN diagnosis Ͼ5 years were linked previously to the racial/ethnic disparity in BP control (lesser control in blacks). 61 The lesser BP control in blacks, however, does not appear to be related to not taking HTN seriously.…”
Section: Nonphysiologic Factors Linked To Poor Bp Controlmentioning
confidence: 99%
“…[9][10][11] The disparity in CVD in blacks may be related to disproportionate levels of psychosocial and environmental stress. [12][13][14][15][16] Randomized, controlled trials of stress reduction using the Transcendental Meditation (TM) program have reported decreases in CVD risk factors, surrogate end points, and mortality in blacks and the general population. [17][18][19][20][21][22][23][24] The overall objective of this trial was to evaluate the effects of practice of the TM program in the secondary prevention of CVD in blacks.…”
mentioning
confidence: 99%